2022
DOI: 10.3390/foods11121725
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Commercial Yeast Starter Cultures on Cabernet Sauvignon Wine Aroma Compounds and Microbiota

Abstract: Commercial Saccharomyces cerevisiae plays an important role in the traditional winemaking industry. In this study, the correlation of microbial community and aroma compound in the process of alcohol fermentation of Cabernet Sauvignon by four different commercial starters was investigated. The results showed that there was no significant difference in the fermentation parameters of the four starters, but there were differences in microbial diversity among the different starters. The wine samples fermented by CE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The role of commercial yeast starter cultures and their effect on the production of volatile compounds in wine and marula fruit wine was investigated. Wang et al [69] reported different types of starter cultures with different effects on the flavour and quality of wine, and the findings revealed that different starter cultures adapt differently to wines of specific variety in specific wine-producing areas. When S. cerevisiae Zymaflore F15, S. cerevisiae 796, S. cerevisiae CEC01 and CECA were inoculated, the total acid was reduced, ranging between 6.2-6.9 g/L and 4.2-4.5 g/L acid in Cabernet Sauvignon wine [69].…”
Section: The Microbial Influence On Quality and Safety Of Marula Winementioning
confidence: 99%
See 1 more Smart Citation
“…The role of commercial yeast starter cultures and their effect on the production of volatile compounds in wine and marula fruit wine was investigated. Wang et al [69] reported different types of starter cultures with different effects on the flavour and quality of wine, and the findings revealed that different starter cultures adapt differently to wines of specific variety in specific wine-producing areas. When S. cerevisiae Zymaflore F15, S. cerevisiae 796, S. cerevisiae CEC01 and CECA were inoculated, the total acid was reduced, ranging between 6.2-6.9 g/L and 4.2-4.5 g/L acid in Cabernet Sauvignon wine [69].…”
Section: The Microbial Influence On Quality and Safety Of Marula Winementioning
confidence: 99%
“…Wang et al [69] reported different types of starter cultures with different effects on the flavour and quality of wine, and the findings revealed that different starter cultures adapt differently to wines of specific variety in specific wine-producing areas. When S. cerevisiae Zymaflore F15, S. cerevisiae 796, S. cerevisiae CEC01 and CECA were inoculated, the total acid was reduced, ranging between 6.2-6.9 g/L and 4.2-4.5 g/L acid in Cabernet Sauvignon wine [69]. Starter cultures in marula fruit wines also showed different aromatic profiles.…”
Section: The Microbial Influence On Quality and Safety Of Marula Winementioning
confidence: 99%
“…Considering that too many spectral indices may lead to redundant information, the study chose the partial least squares-based variable projection importance (PLS-VIP) criterion for independent variable screening [8]. With this criterion, they constructed the spectral indices as a combination of variables in spring and summer seasons as input independent variables for the soil salinity inversion model.…”
Section: Screening Of Spectral Indicesmentioning
confidence: 99%
“…This may be due to the presence of LAB which are not effectively controlled by the bio-protector Candida boidinii. Wang et al [48], in a study on the effect of initiating cultures on aromatic compounds and wine microbiota, showed that wines with a greater population of Leuconostoc and Lactobacillus bacteria were positively correlated with ethyl 9-decenoate. However, no direct relation has yet been established between lactic bacteria and the production pathways of this compound.…”
Section: Final Wine Quality Is Comparable To That Obtained With Somentioning
confidence: 99%